Association between anhedonia and suicidal events in patients with mood disorders: A 3‐year prospective study. Issue 1 (11th July 2020) - Ducasse, Déborah; Dubois, Jonathan; Jaussent, Isabelle; Azorin, Jean‐Michel; Etain, Bruno; Gard, Sébastien; Henry, Chantal; Bougerol, Thierry; Kahn, Jean‐Pierre; Aubin, Valérie; Bellivier, Frank; Belzeaux, Raoul; et al.
Abstract: Background: As almost all mental disorders are associated with increased suicidal‐related behavior, anhedonia might be a trans‐diagnostic dimension to target for suicide prevention. Methods: For this 3‐year‐long prospective study, 2, 839 outpatients with mood disorders were recruited. They were divided in: (a) two groups according to the occurrence or not of suicidal ideation during the follow‐up, and (b) two groups according to the occurrence or not of suicide attempts during the follow‐up. Anhedonia was assessed using a composite score (the French version of the 14‐item Snaith‐Hamilton Pleasure Scale and item 13 of the Quick Inventory of Depressive Symptomatology scale) at inclusion and at 6, 12, 24, and 36 months after inclusion. Results: Patients with mood disorders and anhedonia at least at one follow‐up visit had a 1.4‐fold higher risk of suicidal ideation (adjusted odds ratio = 1.35; 95% confidence interval [1.07, 1.70]), even after adjustment for confounding factors of suicide risk (i.e., bipolar or unipolar disorder, sex, age, marital status, education level, antidepressant intake, personal history of suicide attempt, at least one childhood trauma, and mean of the maximum depression score during the follow‐up). Conversely, association between anhedonia and suicide attempt did not remain significant after adjustment. Conclusions: The significant association between anhedonia and suicide ideation in patients with mood disorders stresses the need of targeting hedonia in mood disorders, and of research focusing on the position to pleasure in life through eudaimonia.